2006
DOI: 10.1111/j.1365-2672.2006.02950.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling salinity inhibition effects during biodegradation of perchlorate

Abstract: Aims:  To determine the mathematical kinetic rates and mechanisms of acclimated perchlorate (ClO)‐reducing microbial cultures by incorporating a term to relate the inhibitory effect of high salinity during biological reduction of concentrated perchlorate solutions. Methods and Results:  Salt toxicity associated with the biodegradation of concentrated perchlorate (200, 500, 1100, 1700 and 2400 mg l−1 as ClO) was investigated using two microbial cultures isolated from a domestic wastewater treatment plant [retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Using a nonlinear curve-fit, the values of the kinetic model parameters (K s and K i ) under different salinity conditions were 268 and 531 (3% NaCl), 830 and 205 (5% NaCl), and 975 and 160 (10% NaCl), respectively. Among these, the values for 3% NaCl conditions were similar to the 295 (K s ) and 575 (K i ) values obtained byPark and Marchand [53]. …”
supporting
confidence: 76%
See 1 more Smart Citation
“…Using a nonlinear curve-fit, the values of the kinetic model parameters (K s and K i ) under different salinity conditions were 268 and 531 (3% NaCl), 830 and 205 (5% NaCl), and 975 and 160 (10% NaCl), respectively. Among these, the values for 3% NaCl conditions were similar to the 295 (K s ) and 575 (K i ) values obtained byPark and Marchand [53]. …”
supporting
confidence: 76%
“…This decrease in perchlorate reduction rate resulted from NaCl toxicity to the perchlorate-reducing microorganisms, implying that its overall growth and enzyme stability were adversely affected. [53] Park and Marchand [53] reported that the inhibitory effects of salinity on perchlorate reduction were significantly different depending on the microbial culture. Anaerobic digester sludge (ADS) cultures are capable of reducing perchlorate at salinities of up to 4% NaCl, while return activated sludge (RAS) cultures were completely inhibited at 4% NaCl.…”
Section: Perchlorate Reduction In Brine At Different Nacl Concentrationsmentioning
confidence: 99%
“…Gingras & Batista (2002) found that a culture enriched from activated sludge yielded only insignificant perchlorate reduction after 550 hours of incubation in 1.5% NaCl. Park & Marchand (2006) were able to acclimate a culture to completely degrade perchlorate in up to 4% NaCl in a stepwise manner and developed a model that included a salinity inhibition term.…”
Section: Introductionmentioning
confidence: 99%
“…Eq. (4) is valid in the range of 0-4% NaCl as indicated by Park and Marchland (2006). Therefore, under 0% NaCl condition I s is equal to zero.…”
Section: The Mathematical Modelmentioning
confidence: 95%
“…Mampaey et al (2015). The biological model includes the influence of the influent salinity both for the autotrophic and heterotrophic biomass (Park and Marchland, 2006). More precisely, the maximum growth rate of both autotrophic and heterotrophic biomass is modelled considering a reduction coefficient (i.e., I s coefficient), assessed as:…”
Section: The Mathematical Modelmentioning
confidence: 99%